Odpowiedź :
[tex]I.~~-2x(x-1)+5(x+4)=-2x^2+2x+5x+20=-2x^2+7x+20\\\\II.~~3a(8a+7b-9)-4a(9a-8b+7)=24a^2+21ab-27a-36a^2+32ab-28a=\\=-12a^2+53ab-55a\\\\III.~~(6x+7y)(3x-8y)=18x^2-48xy+21xy-56y^2=18x^2-27xy-56y^2\\\\IV.~~6(5x-9)(6x+8)=(30x-54)(6x+8)=180x^2+240x-324x-432=\\=180x^2-84x-432\\\\V.(2w+3z)(5w+z)(8w-6z)=(10w^2+2wz+15wz+3z^2)(8w-6z)=\\=(10w^2+17wz+3z^2)(8w-6z)=80z^3-60w^2z+136w^2z-102wz^2+24wz^2-18z^3\\=76w^2z-78wz^2+62z^3[/tex]
Odpowiedź:
⦁ –2x(x – 1) + 5(x + 4) = -2x² + 2x + 5x + 20 = -2x² + 7x + 20
⦁ 3a(8a +7b – 9) – 4a(9a – 8b +7)= 24a² + 21ab - 27a - 36a² + 32ab -28a =
-12a² + 53ab - 55a
⦁ (6x + 7y)(3x - 8y)= 18x² - 48xy + 21xy - 56y² = 18x² - 56y² + 27xy
⦁ 6(5x – 9)(6x + 8)= 6(30x² + 40x - 54x - 72) = 6 (30x² - 14x - 72) =
180x² - 84x - 432
⦁ (2w + 3z)(5w + z)(8w – 6z)= (10w² + 2wz + 15wz + 2z)(8w - 6z) =
(10w² + 17wz + 2z)(8w - 6z) = 80w³ - 60w²z + 136w²z - 102wz² + 16wz - 12z²
= 80w³ + 76w²z - 102wz² + 16wz - 12z²
Szczegółowe wyjaśnienie: